2014
DOI: 10.1371/journal.pone.0096123
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Hyperdense Middle Cerebral Artery Sign Predicts Poor Response to Thrombolysis

Abstract: The aim of our study was to compare the rapid neurological improvement after intravenous recombinant tissue-type plasminogen activator (rtPA) in patients with proximal hyperdense middle cerebral artery sign (p-HMCAS) to those without the sign and those with the distal hyperdense middle cerebral artery sign (d-HMCAS). Admission and 24 hour non-contrast CT scans of 120 patients with middle cerebral artery (MCA) territory stroke who were treated with intravenous rtPA were assessed for the presence of p-HMCAS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…32,33 It was possible that further classification might help to explore additional associations with clinical outcomes. First, the radio- This study suggested that p-HMCAS, rather than d-HMCAS, was associated with more severe neurological deficit and decreased early recovery, which was speculated to be due to a greater clot burden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 It was possible that further classification might help to explore additional associations with clinical outcomes. First, the radio- This study suggested that p-HMCAS, rather than d-HMCAS, was associated with more severe neurological deficit and decreased early recovery, which was speculated to be due to a greater clot burden.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of 148 subjects, HMCAS was This study suggested that p-HMCAS, rather than d-HMCAS, was associated with more severe neurological deficit and decreased early recovery, which was speculated to be due to a greater clot burden. 32,33 It was possible that further classification might help to explore additional associations with clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Patients with more proximal HMCAS are less likely to improve clinically, and HMCAS disappearance is less likely than those with a distally located HMCAS. 1,18 Furthermore, our population age is older than those included in previous studies. 1,8 Some studies suggest patients with cardioembolic stroke or atrial fibrillation are more likely to recanalise with intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 86%
“…28 They indicate a reduced efficacy of IVT. 29 Magnetic resonance imaging: The stroke MRI protocol should aim to be minimalistic and efficient and should be practiced only in hospitals that have the infrastructure to maintain the door-to-needle or door-to-puncture times within the prescribed limits. Every delay of 30 minutes increases the risk of poor functional outcome by 14%.…”
Section: Parenchyma: Assessing the Corementioning
confidence: 99%